Crucial role of the Pht1;4 Gene in Sb(V) tolerance and uptake in Arabidopsis thaliana - Ziyi Dong; Mengchang He; Chunye Lin; Wei Ouyang; Xitao Liu (Ecotoxicology and Environmental Safety)
There has been increasing awareness of the risks of antimony (Sb) in the environment, but the process of Sb(V) absorption by plants and its effects on plants remain unclear. This study focused on four independent T-DNA insertion mutant strains of Arabidopsis thaliana and wild-type (WT) plants to investigate their tolerance, uptake, and response to Sb(V). Compared with those of the WT, the Pht1;4 knockout mutant M-P4 presented greater tolerance to Sb(V) and lower absorption levels. The roots of the M-P4 were longer and the malondialdehyde (MDA) content in the roots of M-P4 was lower than WT (0.194 < 1.333, μM/mg FW). The amount of Sb(V) absorbed by the roots of M-P4 under Sb(V) treatment was lower than that absorbed by WT plants (by 25 %-50 %), and the levels of Sb in the stems and leaves were also lower. Moreover, the transmembrane transport ratio of Sb(V) in M-P4 was lower than that in the WT (0.748 < 0.937). The Pht1;1 knockout mutant exhibited a predominant transmembrane absorption mode for Sb(V), while gene expression data show that knocking out either Pht1;1 or Pht1;4 leads to the upregulation of the other gene. These results collectively demonstrate that the characteristics of M-P4 are due to the important role of Pht1;4 in Sb(V) transport. In summary, this study investigates the influence of several genes on plant tolerance and uptake to Sb(V) and elucidates the crucial role of the Pht1;4 gene, shedding light on the development of Sb phytoremediation strategies and Sb-resistant plants.